Orang Asli suku kaum Orang Kuala antara stereotaip keciciran dengan transformasi: penelitian ke atas penerima gunaan modal insan baharu - Wan Ismail, Wan Ahmad Amir Zal; Hamsan, Hanina Halimatusaadiah; Redzuan, Ma'rof; Abu Samah, Asnarulkhadi (Penerbit Universiti Malaysia Terengganu, 2013)
The stereotypes imposed on Orang Asli as marginalized groups from the mainstream of development is now becoming doubtful. This is because the data and the results of the study some scholars showed the readiness indirectly of Orang Asli participation in a development and acquire positive impact from them. The Indicator is the adoption of a new human capital differently with traditional human capital by Orang Asli. While the stereotype is giving the impression that Orang Asli community is a group that lived isolated from mainstream society and have not the human capital as mainstream society. To examine the reality, this article listed two objectives to be achieved, namely to identify the ownership and the usage new human capital and compare them amongst fishermen and businessmen. These two objectives as indicators whether Orang Asli is still left out of the mainstream development or vice versa. This study applied survey research design on 267 Orang Asli amongst Orang Kuala in Batu Pahat and Pontian, Johor. Result showed that Orang Kuala had use new human capital. However, the ownership and use new of human capital vary by the employment type of Orang Kuala. The ownership and use new of human capital can be interpreted as a sign of Orang Kuala participation in the mainstream development, and thus rejected stereotypes of Orang Asli as a marginalized group from the mainstream development.